REFLEXION SUR L’ENSEIGNEMENT DES MATHEMATIQUES DANS LES ECOLES SECONDAIRES - Ghislain KUMBUKA KALIHOFU; NYAKABEJI , OMBENI Conscient (IJRDO -JOURNAL OF MATHEMATICS, 2021)
This article answers the main question: "What is the meaning of mathematics in practical life? "which thousands of people are asking themselves and which most mathematics teachers do not know how to answer. It aims to identify and address the causes of school failure and the reasons for disinterest (lack of interest) in learning mathematics. didactic techniques or procedures for teaching the mathematics course that can lead students to assimilate, enjoy and practice it have been proposed for mathematics teachers. Typical and practical examples supporting these techniques, counter-examples and comments are proposed in a detailed manner. An experiment in different classes in the surveyed schools in order to verify the level of adaptation by the learners was carried out. Attached to this article is a survey questionnaire addressed to mathematics teachers and their pupils